Anticipated Engagement in a Village Organization for Aging in Place. Issue 45 (8th August 2019) - Gammonley, Denise; Kelly, Annette; Purdie, Robert
Abstract: Although older adults prefer maintaining residence independently in the community as they grow older it is not always possible due to impairments, isolation, and changing health needs. Villages, an emerging consumer-directed care model providing social engagement and services, support aging in place. To be viable organizations villages must attract and enroll sufficient numbers of members. This study examined factors associated with older adults anticipated engagement as a village member. Using a cross-sectional survey design community residing older adults ( N  = 193) identified predisposing, enabling, and need factors associated with anticipated engagement. Participants rated anticipated engagement between "Slightly Unlikely" and "Likely" (Mean = 2.71, SD = 1.31). A model including predisposing and enabling factors produced the best overall fit [−2 Log likelihood = 246.514, χ2(8) = 20.414, p . = .008] correctly classifying 61.1% of cases and explaining 13.4% of the variance according to the Nagelkerke R 2 statistic. Older adults who engage in preventative health behaviors may be predisposed to joining a village as well as those who are already engaging in supportive acts of neighboring. Villages might consider these factors in designing outreach and service programing. Future research should identify how factors such as income and personal health practices contribute to interest in village membership.